Education and Workshop Improve Healthcare Workers' Knowledge of Laboratory Examination for the Diagnosis of Superficial Dermatomycosis - Ervianti, Evy; Astari, Linda; Rahmadewi; Setyaningrum, Trisniartami; Mappamasing, Hasnikmah; Anggraeni, Sylvia; Widia, Yuri; Ngesti Kumalasari, Diah; Axelia, Presstisa Gifta; Hadiwidjaja, Farsha Naufal; Sunarto, Olivia Awwalin; Kathrin Kezia Henry; Sulaksanaswastho Suyoso; Puspowati, Erindah (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2023)
Background: Superficial dermatomycosis is one of the most prevalent skin diseases worldwide. The diagnosis of  superficial dermatomycosis is established clinically, and supported by several examinations, such as microscopic examination, fungal culture, and Wood's lamp examination for certain species. Purpose: This study is to evaluate the improvement of the knowledge of general practitioners and medical analysts after education and workshop. Methods: This cross-sectional observational study involved 70 subjects, consisting of 35 general practitioners and 35 medical analysts from 35 public health centers in Bojonegoro who were willing to participate in this study. The level of knowledge was assessed before and after the health education on laboratory examination for the diagnosis of superficial dermatomycosis. Result: There was a significant difference in mean scores between the pre-test and post-test after health education (p = <0.001). The mean knowledge score of the pre-test before intervention among general practitioners was 36.57 ± 19.088, which increased to 68.00 ± 13.240, and the mean knowledge score before intervention among analysts was 27.14 ± 13.842, which increased to 62.00 ± 12.078 after health education intervention. Conclusion: Following health education, there was an improvement in the healthcare workers's knowledge of laboratory examinations for the diagnosis of superficial dermatomycosis